Pemanfaatan Biji Rambutan Sebagai Serum Wajah Untuk Mengurangi Jerawat - Agus Susanti; Hanida Asma Nafi’ah (Garina, 2023)
Rambutan is a seasonal fruit that is easy to find in tropical areas like Indonesia. Rambutan seeds contain fat, polyphenols (flavones, flavonoids, resveratrol, and isoflavones, and vitamin C. Fophenols in rambutan seeds function to increase anti-inflammation and reduce acne. The study was conducted by methods of observation, documentation, literature, experiments, questionnaires and questionnaires. The composition is 8 pcs rambutan seeds, 120 ml of ethanol, 15 ml of olive oil, 1 tsp of vegetable glycerin. This research aims to find out and explain the manufacturing process, benefits and public acceptance of rambutan seed serum The sensory test of the two validators, namely thick serum and the ingredients for making Face Serum is correct. Use of facial serum is carried out 2x a day, in the morning after washing your face and at night before going to bed, to get results. Public test results on 35 respondents to find out public acceptance, 97 % of respondents liked the use of rambutan seeds as a facial serum, 100% of respondents liked the brownish yellow color, 100% of respondents liked the fragrant aroma of olive oil, 100% of respondents liked the non-coarse texture, 100% of respondents liked facial serum which when applied directly sticks to facial skin . It can be concluded that the use of rambutan seeds as a facial serum to reduce acne is a new product innovation in the field of beauty. Clinical trials and product durability tests are needed for rambutan seed as a facial serum to reduce acne.